Una nuova specie di Dysmicoccus Ferris (Homoptera Coccoidea Pseudococcidae) dall'Italia (Bollettino di zoologia agraria e bachicoltura, 2024)
A description is given of the adult female of Dysmicoccus psoraleae, sp. n., living on Psoralea bituminosa L. in Sicily (Italy).
Keywords: Dysmicoccus psoraleae sp. n.; mealybug; Psoralea bituminosa L.; Italy